Evaluation of lightning warning technique with multi-source data for Vung Tau coastal area - Hoang, Hai Son; Nguyen, Xuan Anh; Pham, Xuan Thanh; Pham, Le Khuong; Nguyen, Hiep Van (Vietnam Journal of Marine Science and Technology, 2023)
In this paper, the authors used multi-source data, including the electric field data observed by EFM-100C at Rescue Station No. 1 on the “Bai Sau” beach in Vung Tau coastal area for 166 days from May to October 2019; Himawari satellite data and Nha Be weather radar data and the GLD-360 lightning position data to evaluate the lightning warning method. Radar and satellite data were used to determine deep convective clouds. The GLD-360 lightning position data were used to examine the consistency of lightning location with the deep convective clouds. The “two areas” method was applied. The Area of Concern (AOC) has a radius of 10 km from the electric field measurement station. The Warning Area (WA) is 20 km extending from the outermost AOC area. Due to the influence of sea-salt aerosol on the background electric field intensity, the electric field threshold selected for a warning is larger than the absolute value (1.5 kV/m). The results showed that the probability of detection (POD), failure to warn (FTW), and false alarm ratio (FAR) were 86.3%, 13.07%, and 23.17%, respectively. The average time of lightning warning for the Vung Tau coastal area is 23 minutes in advance. The warning time is equivalent to that in some studies around the world. The value is suitable for practical application in lightning prevention on the beach and in the Vung Tau coastal area.